(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Training healthcare providers on early detection and use of the first response bundle for postpartum hemorrhage (PPH) cases was one of the key strategies used in the intervention facilities during the E-MOTIVE trial. Results published from the E-MOTIVE trial revealed a marked reduction of 60% in the severity of PPH, idicating the need to implement the same approaches in the 11 control arm facilities. Methods: Healthcare providers (HCPs) from the 11 sites were trained on the E-MOTIVE bundle and issued with PPH emergency trollies, mannequins, and blood pressure machines. The staff was also mentored on self-PPH audits and feedback mechanisms from the data generated monthly from the labor ward. Two days of on-site training were conducted for the staff, which included knowledge tests (before and after) and skills assessment (objective skilled clinical examinations (OSCES)). EMOTIVE champions were identified from the training to promote ongoing skills practice sessions at the facility level. Monthly follow-ups were cpnducted to track individual progress using the training tracking sheet. Results: The HCPs cited confidence in detecting and treating PPH after the training with the hospitals demonstrating readiness in managing PPH through the presence of PPH emergency trollies. There was increased teamwork among the HCPs with improved documentation practices in the labor wards. Conclusion: Adoption of a sustainable training approach for healthcare providers in the prevention, early detection, and treatment of PPH that incorporates evidence-based strategies is key to improving maternal outcomes. National and county ministries of health have demonstrated a commitment to leverage the E-MOTIVE bundle approach after remarkable findings.